Tongxinluo Improves Cardiac Function and Ameliorates Ventricular Remodeling in Mice Model of Myocardial Infarction through Enhancing Angiogenesis. (27th August 2013) - Bai, Wen-Wu; Xing, Yi-Fan; Wang, Bo; Lu, Xiao-Ting; Wang, Ying-Bin; Sun, Yuan-Yuan; Liu, Xiao-Qiong; Guo, Tao; Zhao, Yu-Xia
Abstract : Background . Myocardial infarction (MI) is a major cause of morbidity and mortality in the world. Tongxinluo (TXL) is a traditional Chinese compound prescription which has cardioprotective functions. The present study was aimed to determine the effect of TXL on postischemic cardiac dysfunction and cardiac remodeling and to elucidate the underlying mechanisms. Methods and Results . MI was performed by ligation of left anterior descending coronary artery (LAD) in male adult mice. Mice were randomly divided into four groups: (1) sham group (Sham); (2) MI-control group (Control); (3) MI-low dose TXL group (TXL-L); and (4) MI-high dose TXL (TXL-H) group. Compared with the control group, TXL treatment restored cardiac function, increased revascularization, attenuated cardiomyocyte apoptosis, and reduced interstitial fibrosis. TXL treatment increased the phosphorylation of Akt, extracellular signal regulated kinase (ERK), and endothelial nitric oxide synthase (eNOS); the expression of phosphatidylinositol3-kinase (PI3K), hypoxia-inducible factors 1 α (HIF-1 α ), and vascular endothelial growth factor (VEGF); and the DNA binding activity of HIF-1 α after MI. Conclusion . TXL may improve cardiac function and ameliorate cardiac remodeling by increasing neovascularization through enhancing the phosphorylation of Akt and ERK, the expression and activity of HIF-1 α, and the protein level of VEGF and p-eNOS.